'The One Who is Speaking' in Hebrews 12:25 - Gene Smillie (Tyndale Bulletin, 2004)
This treatment of whether the author refers to Jesus, or more generally to God, as ‘the one who is speaking’ (ὁ λαλῶν), in Hebrews 12:25 takes into account the possible relationship of the nearly identical participles λαλοῦντι in verse 24b and τόν λαλοῦντα in verse 25a. The antecedent of λαλοῦντι in verse 24 is problematic; many translations refer to ‘the blood that speaks better than the blood of Abel’, but this interpolation may be misleading. The author’s argument in the near context suggests that the one now speaking from heaven is the same God who spoke from Sinai on earth. The added implication that he speaks through the author’s own written words is significant for understanding the hermeneutic of Hebrews.